Non-invasive monitoring of training load in athletes by wearable sensors - Düking, P.; Achtzehn, S.; Sperlich, B. (Science and Skiing VII, 2018)
The aim of this article was to outline relevant external and internal parameters monitored by wearables to increase performance and decrease likelihood of injuries or illnesses. We advise carefully evaluation of the reliability and validity of a device before applying it in a monitoring process.